Hepatitis B and C: a current problem in the group of infectious diseases in the nursing/midwifery profession - Rybka, Agnieszka; Marć, Małgorzata S.; Barnaś, Edyta (Nursing Problems / Problemy Pielęgniarstwa, 2025)
The doubling of vaccination against hepatitis B contributes to a decrease in new infections. The aim of the study was to discuss issues related to infectious diseases in the nursing/midwifery profession, using hepatitis B and C as an example, in the context of the available hepatitis B vaccine. A review of the literature from 2008-2023 related to hepatitis B vaccinations in the workplace was conducted via the MEDLINE/PubMed database, as well as reports on occupational diseases, hepatitis B and C cases, and mandatory hepatitis B vaccinations among healthcare personnel. The total number of hepatitis B cases in 2018-2022 in Poland was 11,090, and hepatitis C cases 11,512. The number of people vaccinated against hepatitis B has remained at a similar level since 2020. The most effective form of prevention of infectious diseases of occupational etiology in a nurse midwife’s workplace is vaccination against hepatitis B.